The influence of humidity on the parameters of an electric signal under pulsed mechanical excitation of heterogeneous materials containing piezoelectric inclusions; Russian Journal of Nondestructive Testing; Vol. 47, iss. 6 - Fursa T. V. Tatyana Viktorovna; Dann D. D. Denis Dmitrievich; Osipov K. Yu. Konstantin Yuryevich; Nesteruk D. A. Denis Alekseevich (2011, 2011)
Title screen